Violent crimes and their implications for regional development: a literature review (Research, Society and Development, 2020)
This study discusses the implications of lethal and intentional violent crimes - LIVC on regional development, crimes that affect quality of life and social well-being, as well as socioeconomic development. We used articles published in recent years, which met the inclusion and exclusion criteria, where 25 papers that met the pre-established criteria were selected, thus being evaluated and analyzed, contributing this way to the production this review. We identified factors, which are associated with the increase and reduction of LIVC and its consequences on regional development. As findings indicate that better opportunities in education, decent-paying employment, income, civil society mobilization, more governed state policies, are aspects capable of reducing intentional lethal violent crimes.